Case Report: Mycobacterium senegalense Infection After Cholecystectomy - Zhou, Huiling; Yang, Hong; Gong, Fengling; Zhou, Shaolong; Yang, Yifeng; Liu, Haidan; Liu, Jijia (Frontiers in Public Health, 2022)
Background Mycobacterium senegalense is a non-tuberculous mycobacterium and is found everywhere in the environment. However, M. senegalense infection in human is extremely rare, especially in immunocompetent individuals. It is difficult to detect M. senegalense infection because its symptoms are non-specific, and routine diagnostic tests are less sensitive. It is also resistant to commonly used antibiotics. Here, we report the first case of M. senegalense infection after laparoscopic cholecystectomy in China. Case Presentation A 55-year-old man was admitted because of repeated infections at multiple incision sites for more than 1 year. Although routine diagnostic test results were negative, metagenomic next-generation sequencing (mNGS) identified DNA sequences of M. senegalense in tissue samples from incision sites. The presence of M. senegalense was further confirmed by polymerase chain reaction and capillary electrophoresis. After 60 days of quadruple therapy with clarithromycin, moxifloxacin, rifampicin, and oxycycline, the patient's wound healed. Conclusion We believe the case findings contribute to the limited amount of knowledge about M. senegalense infection and raises awareness that this infection can result in poor wound healing, even in an immunocompetent host. Owing to a lack of early, precise diagnosis, it is difficult to treat M. senegalense infections. Based on our findings, mNGS is a sensitive diagnostic test for M. senegalense infections.